Coopetition in supply chains: A case study of a coopetitive structure in the horticulture industry - Wood, Lincoln (Business Science Reference (an imprint of IGI Global), 2012)
Supply chain management has been increasingly seen as a strategic tool to improve the competitiveness of companies. Coopetition, the mingling of competitive and cooperative relationships, has been utilised by New Zealand companies in the horticulture industry to help break into and develop new markets. Using a case study various elements of the supply chain are examined from both strategic and operational perspectives for this group of companies and their customers and suppliers. The connections to the customer are shown to be enhanced through careful implementation, as the group of companies act to adjust their entire supply chains to make them increasingly customer-orientated. Significant benefits that are shown to accrue include improved information flow, increased ability to supply, and flexibility to meet customer requirements.